2023
DOI: 10.3390/buildings13020476
|View full text |Cite
|
Sign up to set email alerts
|

CRITIC-TOPSIS-Based Evaluation of Smart Community Safety: A Case Study of Shenzhen, China

Abstract: As a micro-unit of the smart city, smart communities have transformed residents’ lives into a world that connects physical objects. Simultaneously, though, they have brought community safety problems. Most studies of the smart community have only focused on technical aspects, and little attention has been paid to community safety. Thus, this paper aims to develop an evaluation system for smart community safety, which will further promote community safety development. On the basis of identifying evaluation indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…Then, it can be concluded that the level of the RSG was high for M1 to M30, and M31 has medium performance. The results represented that no smart community was at the low and lowest level, which means that good performance was achieved by 31 smart communities in terms of the RSG in smart communities [23].…”
Section: The Results Of Evaluation Of the Rsg Through The Fce Methodsmentioning
confidence: 96%
See 3 more Smart Citations
“…Then, it can be concluded that the level of the RSG was high for M1 to M30, and M31 has medium performance. The results represented that no smart community was at the low and lowest level, which means that good performance was achieved by 31 smart communities in terms of the RSG in smart communities [23].…”
Section: The Results Of Evaluation Of the Rsg Through The Fce Methodsmentioning
confidence: 96%
“…As for the RSG in smart communities, based on the results, the highest score for 31 sample communities was 69.08, while the lowest score was 56.92. Considering the range of values of performance, it can be divided into 5 levels of the total score, namely, highest level (80~100), high level (60~80), medium level (40~60), low level (20~40), and lowest level (0~20) [23]. Then, it can be concluded that the level of the RSG was high for M1 to M30, and M31 has medium performance.…”
Section: The Results Of Evaluation Of the Rsg Through The Fce Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IFSs [ [70] , [71] , [72] , [73] ] are an efficient tool for conducting uncertain information during the performance evaluation of CSR from the perspective of environmental accounting. Until now, no or few techniques were studied on CRITIC [ [74] , [75] , [76] , [77] , [78] , [79] , [80] ]and CoCoSo in light with CSM under IFSs. Therefore, in this study, the IFN-CSM-CoCoSo is conducted for MAGDM with IFSs.…”
Section: Introductionmentioning
confidence: 99%